The Effect of Application of The Brain-Based Learning (BBL) Approach on The Connection Ability of Students - Anisa Fitri; Ahmad Zaeni (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
This research is based on the low ability of students' mathematical connections. A learning approach that can improve students' mathematical connection ability is the Brain-Based Learning (BBL) approach. The purpose of this study is to determine whether there is influence from the application of the Brain-Based Learning (BBL) approach to students' mathematical connection ability. The method used in this research is quantitative research (experimental study) with One-Shot Case Study Design research design. This study's sample is the students of class X.MIPA.4 consisting of 28 students obtained by simple cluster random sampling technique. The instrument used in this research is using the questionnaire and test. The data analysis technique used is the linear regression test. From a hypothesis test, t-count > t-table is 4,003> 1,710, then H0 is rejected, and Ha accepted. So it can be concluded that there is a positive influence of applying the Brain-Based Learning (BBL) approach to students' mathematical connection ability with a considerable influence equal to 37.5%.Â Â